Multidrug-resistant tuberculosis in KwaZulu-Natal, South Africa: An overview of patients' reported knowledge and attitudes - Jayneetha Maharaj; Andrew Ross; Niren R. Maharaj; Laura Campbell (AOSIS, 2016)
Background: The incidence and prevalence of multidrug-resistant tuberculosis (MDR TB) in the province of KwaZulu-Natal, South Africa, are amongst the highest in the world. Previously, interventions have been largely biomedical based; however, there is growing opinion that interventions must include social aspects such as patient education and attitudes. Methods: This observational study assessed the knowledge and attitudes of 380 patients diagnosed with MDR TB at a centralised MDR TB unit in Durban. Data were collected using a questionnaire that was distributed to every third patient attending the outpatient MDR TB clinic. Data were collected over an 8-week period and analysed descriptively. Results: Just under half of the respondents had primary MDR TB. Most respondents were young, female unemployed and did not receive a social grant. Knowledge around diagnosis of MDR TB was generally adequate. There were important misconceptions about spread of the disease and duration of treatment. Most respondents received knowledge of MDR TB from healthcare workers. Some respondents received knowledge from friends, family and Sangomas and believed that the disease was caused by bewitchment or as a form of punishment. Discussion: The need for strengthening the role of primary care physicians in promoting education and providing support is highlighted. Further study is needed to investigate the high rate of primary MDR TB and to identify the unique challenges faced by women who have MDR TB. Future research could include the possibility of involving traditional healers in a contextually sensitive MDR TB education, training and support programme.